Interface Concentrated‐Confinement Suppressing Cathode Dissolution in Water‐in‐Salt Electrolyte. Issue 36 (6th August 2020) - Yue, Jinming; Lin, Liangdong; Jiang, Liwei; Zhang, Qiangqiang; Tong, Yuxin; Suo, Liumin; Hu, Yong‐sheng; Li, Hong; Huang, Xuejie; Chen, Liquan
Abstract: Mass dissolution is one main problems for cathodes in aqueous electrolytes due to the strong polarity of water molecules. In principle, mass dissolution is a thermodynamically favorable process as determined by the Gibbs free energy. However, in real situations, dissolution kinetics, which include viscosity, dissolving mass mobility, and interface properties, are also a critical factor influencing the dissolution rate. Both thermodynamic and kinetic dissolving factors can be regulated by the ratio of salt to solvent in the electrolyte. In this study, concentration‐controlled cathode dissolution is investigated in a susceptible Na3 V2 (PO4 )3 cathode whose time‐, cycle‐, and state‐of‐charge‐dependent dissolubility are evaluated by multiple electrochemical and chemical methods. It is verified that the super‐highly concentrated water‐in‐salt electrolyte has a high viscosity, low vanadium ion diffusion, low polarity of solvated water, and scarce solute−water dissolving surfaces. These factors significantly lower the thermodynamic‐controlled solubility and the dissolving kinetics via time and physical space local mass interfacial confinement, thereby inducing a new mechanism of interface concentrated‐confinement which improves the cycling stability in real aqueous rechargeable sodium‐ion batteries. Abstract : This super‐highly concentrated water‐in‐salt electrolyte has a high viscosity, low vanadium ion diffusion, low polarity of solvated water, and scarce solute−water dissolving surfaces. These factors significantly lower the thermodynamic‐controlled solubility and the dissolving kinetics, thereby inducing time and physical space local mass interfacial concentrated‐confinement that improves cycling stability in aqueous rechargeable batteries.